The Analysis of Phrasal Verbs and Its Vicinity in Elizabeth Gilbert's Eat, Pray, Love - Octa Pratama Putra (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
The aim of this study earnestly regards to the forefront of phrasal verbs and its vicinity. After the writer reaps the phrasal verb, the writer contrives them into four sub-divisions: they are: intransitive, transitive, inseparable, and separable phrasal verb. The data are collected from Eat, Pray, Love novel by Elizabeth Gilbert. The result shows that, they are shown 20 phrasal verbs; they are 17 transitive phrasal verbs, 5 intransitive phrasal verbs, 3 separable phrasal verbs, and 10 inseparable phrasal verbs. The conclusion tells, within the novel, it has been classified all about the phrasal verbs the writer has been conducted yet. Concerning to the four classifications of phrasal verbs that the writer has scoped and found out, hereby it is stated that phrasal verb, definitely, has an exact definition. Certainly, it needs an understanding of current context first (read and understand in a certain dialogue or conversation inside that novel of Eat, Pray, Love) to know what the meaning of that case or topic being conveyed is.